Improving Students' Scientific Argumentation Ability through Argument-driven Inquiry Learning with Procedural E-Scaffolding - Husen Jauwad; Supriyono Koes Handayanto; Markus Diantoro (Pascasarjana Universitas Negeri Malang (UM), 2021)
Abstract: Scientific argumentation is a communication technique that needs to be improved in the 21st century. Scientific argumentation research using argument-driven inquiry learning with procedural e-scaffolding is still limited. In this work, we report the results of a study combining argument-driven inquiry learning with procedural e-scaffolding. This research was conducted in three classes which were divided into the ADI-ES class, the ADI class, and the control class. Learning is carried out online so that data is collected using Google Forms. Furthermore, the data were analyzed using ANOVA and the post hoc test. The results showed that there were differences in the ability of scientific argumentation before and after learning. Among the three classes, ADI-ES class has better scientific argumentation skills than other classes. Furthermore, the comment feature on Google Docs might be used to support e-scaffolding during learning.Abstrak: Argumentasi ilmiah merupakan teknik berkomunikasi yang perlu ditingkatkan pada abad 21. Penelitian argumentasi ilmiah yang menggunakan pembelajaran argument-driven inquiry dengan e-scaffolding prosedural masih terbatas. Di artikel ini kami melaporkan hasil penelitian yang mengombinasikan pembelajaran argument-driven inquiry dengan e-scaffolding prosedural. Penelitian ini dilakukan pada tiga kelas yang dibedakan menjadi kelas ADI-ES, kelas ADI, dan kelas kontrol. Pembelajaran dilakukan secara daring sehingga data dikumpulkan menggunakan bantuan google form. Selanjutnya, data dianalisis menggunakan ANOVA dan uji pos hoc. Hasil penelitian menunjukkan bahwa terdapat perbedaan kemampuan argumentasi ilmiah sebelum dan sesudah pembelajaran. Diantara ketiga kelas, kelas ADI-ES memiliki perubahan kemampuan argumentasi ilmiah yang lebih baik daripada kelas lainnya. Selanjutnya fitur komentar pada google doc dapat dimanfaatkan lebih lanjut untuk mendukung e-scaffolding saat pembelajaran berlangsung.